2017
DOI: 10.3390/w9010023
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Evapotranspiration Coefficients in a Temperate Maritime Climate Using the METRIC Model and Landsat TM

Abstract: Abstract:The applicability of a land surface temperature (LST)-evapotranspiration (ET) regression model to estimate ET fraction (ETrF) was tested in the temperate maritime climate of Central Ireland. In this study, the Mapping ET at high Resolution and with Internalized Calibration (METRIC) model was applied to calculate evapotranspiration from a mixed land cover area in Central Ireland. The ETrF values estimated on a pixel-by-pixel basis using two different surface roughness maps derived from two different es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…It is imperative to perform independent validation of the methodology. For this reason, a new satellite image of Landsat ETM+, taken in 2015, was used to compare the ET r F values calculated by the proposed method and the respective values acquired using the METRIC methodology, which is considered as benchmark [58]. This is also supported by the fact that Earth Engine Evapotranspiration Flux (EEFlux), which is a web-based tool operating on the Google Earth Engine and computational cloud, uses the METRIC model as foundation [58,71].…”
Section: Validation Of the Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to perform independent validation of the methodology. For this reason, a new satellite image of Landsat ETM+, taken in 2015, was used to compare the ET r F values calculated by the proposed method and the respective values acquired using the METRIC methodology, which is considered as benchmark [58]. This is also supported by the fact that Earth Engine Evapotranspiration Flux (EEFlux), which is a web-based tool operating on the Google Earth Engine and computational cloud, uses the METRIC model as foundation [58,71].…”
Section: Validation Of the Methodologymentioning
confidence: 99%
“…EVI2 is a very convenient variation of Enhanced Vegetation Index (EVI) as explained in [49,56,57]. Those indices use only two spectral bands for their formulation, resulting in relatively easy processing, which is a very important parameter in choosing them for processing, along with previous experience [33,36,58]. The related formulas used for the computations of the above indices are:…”
Section: Landsat 7 Etm+ and In-situ Ger1500 Data Availabilitymentioning
confidence: 99%
“…(2011a, 2011b), Spiliotopoulos et al . (2017) and Mokhtari et al . (2019) state that a single cloud‐free satellite image is decent enough in the estimation of seasonal ET.…”
Section: Methodsmentioning
confidence: 97%
“…Since the study region is coastal buffered, due to high cloud cover and comparatively less temporal resolution, the number of Landsat image matches with the Sentinel overpass is relatively less. For each study year, we identified two Landsat that imbricated Sentinel considerably with little cloud cover except 2016 (Spiliotopoulos et al, 2017; Mokhtari et al ., 2019; Niu et al ., 2019; Runge and Grosse, 2019). There were hardly any changes observed on the site among the Landsat 8 and Sentinel 2 same‐day observations.…”
Section: Site Description and Data Usedmentioning
confidence: 99%
“…Finally, it is important to indicate that the number of days with a complete data set (satellite images and EC fluxes) was limited by cloudiness when the satellite overpassed the experimental site and persistent noise of the EC system (instrumental problems and flow distortion through the tower). For these reasons, several researchers have used a limited number of images to evaluate the satellite-based remote sensing (SBRS) models [6,[45][46][47][48][49].…”
Section: Image Processingmentioning
confidence: 99%